The work and relatedness of ties mediated online in supporting long‐term condition self‐management. Issue 3 (25th November 2019) - Allen, Chris; Vassilev, Ivaylo; Kennedy, Anne; Rogers, Anne
Abstract: The 'care transition' is characterised by reduced state involvement in chronic illness management in response to socio‐political movements aimed at meeting the challenges presented by an increased prevalence of chronic illness. Amongst these changes has been online communities' rising importance in everyday interactions and attention is being increasingly paid towards the ways online contacts might contribute to self‐management. Whilst research has illuminated the relevance of personal networks in long‐term condition management, it is relevant to extend this work to consider the place of ties mediated online in this bricolage of support, including better understanding the work drawn from them and the strategies involved in eliciting it. This study examined the work and relatedness of 30 participants, who used online communities. Participants were asked about the role of on and offline ties and ego network mapping was used to frame conversations about the nature of this support. The context of engagement followed three main themes. Participants drew from online communities in response to deficits in offline support, they used online ties to leverage support or action from offline ties and they used online ties to substitute offline support, with less intimate online ties.